HUBUNGAN KEPEMIMPINAN DAN KEMAMPUAN MANAJERIAL DENGAN KINERJA KEPALA SEKOLAH SMA KOTA PEMATANSIANTAR SUMATERA UTARA - Said Hutagaol; Melisa Nur Asima Sidabutar (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2013)
There is something wrong in education in Indonesia.Nowdays the quality of education in Indonesia has not shown an improvement.The reality on the ground shows that there are many principals who have not demonstrated optimalization performance. The condition of schools is very poor. The majority of the schools have a new functional needs, not minimum requirements. The principals must create the quality of the school to primary responsibility. For optimalization performance, the principal must fullfill themselves with the leadership and managerial skills.The thesis aims to reveal the relation of leadership and managerial skills with performance principal High School Pematangsiantar North Sumatera. The research of the analyzed descriptively using the method of survey and correlation techniques.The result showed that the value of the correlation coefficient of the leadership the principal and performance is equal to 0.702 while the coefficient of determination is it mean the relationship with leadership of the performance principal by 49 % and through every 1 regression equation Å¶= - 5.8853 + 1.056 X1. It shows kindness the leadership will raise the performance of the principal of 1.056.The value of the correlation coefficient managerial skills of the principal performance is equal to 0.616 while the coefficient of determination is that the managerial skills with the performance principal by 38 % and through every 1 regression equation Å¶= 15.580 + 0.892 X2. It shows kindness the managerial skills with raise the performance of the principal of 0.892.The correlation of leadership and managerial skill to the performance of the principal is equal to 0.777 meanwhile through the coefficient or determination is known that the leadership and managerial skills with the performance principal by 60.4% and the double regression equality of Å¶ = -26.106 + 0.8 X1 + 0.542. It shows kindness the leadership with raise the performance of the principal of 0.8 and managerial skill with raise the performance of the principal of 0.542.It means the relation of leadership and managerial skill with performance principals have a strong and significant relationship. It is essential for all high school principals having and implemented leadership and managerial skills in order to optimaliz the quality and the performance of principals.Keywords : Leadership, managerial skill, performance principals.